Psychometric evaluation and community norms of the PHQ-9, based on a representative German sample - Kliem, Sören; Sachser, Cedric; Lohmann, Anna; Baier, Dirk; Brähler, Elmar; Gündel, Harald; Fegert, Jörg M. (Frontiers in Psychiatry, 2024)
BackgroundThe Patient Health Questionnaire (PHQ-9) is a popular tool for assessing depressive symptoms in both general and clinical populations. The present study used a large representative sample of the German adult population to confirm desired psychometric functioning and to provide updated population norms.MethodsThe following psychometric properties were assessed: (i) Item characteristics (item means, standard deviations and inter-item correlations), (ii) Construct validity (correlations of the PHQ-9 sum-score with scores obtained from instruments assessing depression, anxiety and somatization (GAD-7, BSI-18), (iii) Internal consistency (coefficient omega), (iv) Factorial validity (via confirmatory factor analysis of the assumed one factorial model) as well as (v) Measurement invariance (via multi-group confirmatory factor analyses across gender, age, income and education).ResultsThe study found that the PHQ-9 had sound psychometric properties in terms of internal consistency and construct validity, and that measurements obtained with the tool could be compared across gender and age.LimitationsDespite using a representative sample, the response rate was only 42.6%. Furthermore, diagnostic efficiency cannot be assessed as there were no clinical interviews conducted. Conclusion: The updated population based norms, which are presented for the total sample as well as separated by gender and various age-groups, provide a useful reference for clinical practice and epidemiological research.